Pengaruh Pemberian Takaran Pupuk Kandang Ayam Pada Tanah Ultisol Terhadap Pertumbuhan Dan Hasil Pakcoy - Permono, Muhammad Sidiq; Purnomo, Joko; Zairin, Zairin (Universitas Lambung Mangkurat, 2023)
Pakcoy (Brassica rapa L.) is a horticultural commodity that is much needed and favored by the community because of its good taste, ease to get and cultivation is not too difficult. The higher the level of human awareness of healthy living, the need for mustard vegetables in the country also increases. Given the economic value and health benefits, it is natural that efforts to increase production continues. The research was conducted for four months starting from October 2019 to January 2020. Located on Jl. Ahmad Yani Km 36, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru City, South Kalimantan Province. The design used is a Single-factor Randomized Design (RAL) that is a measure of chicken manure (P) consisting of five levels of treatment repeated four times so that 20 experimental units were obtained. The results showed that the provision of chicken manure in the soil ultisol has a real effect on the number of pakcoy leaves aged 20 days after planting, while other parameters have no real effect. The provision of chicken manure dose of 10 tons ha-1 (p2) equivalent to 20 grams per polybag produces a top weight of 105.50 grams.